Effect of Bian-stone ironing and rubbing combined with Traditional Chinese Medicine penetration and auricular acupont pressing therapy in relieving the bloating and gastric pain of patients with chronic gastritis (砭石熨摩中药透入法联合耳穴贴压缓解慢性胃炎胃痛、胃胀症状效果观察) - XUE Li (薛丽); WANG Guifang (王贵芳) (Association of Integrative Nursing, 2024)
Objective To investigate the effect of Bian-stone ironing and rubbing combined with Traditional Chinese Medicine penetration and auricular acupont pressing therapy in relieving the bloating and gastric pain of patients with chronic gastritis. Methods Totally 60 patients with chronic gastritis were randomly divided into the observation group and control group, with 30 cases in each group. All patients received routine symptomatic treatment and nursing, and patients in the observation group received Bian-stone ironing and rubbing combined with Traditional Chinese Medicine penetration and auricular acupoint pressing therapy. The time to relief of bloating and gastric pain was recorded, and effect of interventions was compared between two groups. Results The time to relief of bloating and gastric pain in the observation group was shorter than that in the control group, with a significant difference (P＜0. 05). The total effective rate was 80. 00%(24/30) in the observation, which was higher than 60. 00%(18/30) in the control group, with a significant difference(P＜0. 05). Conclusion The Bian-stone ironing and rubbing combined with Traditional Chinese Medicine penetration and auricular acupont pressing therapy are effective to relieve the bloating and gastric pain of patients with chronic gastritis. (目的 探讨砭石熨摩中药透入法联合耳穴贴压缓解慢性胃炎胃痛、胃胀临床症状的效果。方法 将60例慢性胃炎患者随机分为观察组和对照组, 各30例。对照组常规对症治疗, 观察组在对照组基础上实施砭石熨摩中药透入法联合耳穴贴压疗法。记录两组胃痛、胃胀症状消失时间, 比较两组临床总有效率。结果 观察组胃痛、胃胀症状消失时间均短于对照组, 差异有统计学意义(P＜0. 05)。观察组总有效率80. 00%(24/30), 高于对照组的60. 00%(18/30), 差异有统计学意义(P＜0. 05)。结论 砭石熨摩中药透入法联合耳穴贴压兼具温经通络、理气止痛、活血通络等作用, 能有效缓解慢性胃炎患者胃痛、胃胀症状。)